A) 0,2 razy (¾ : sześć ósmych - 4,5 + 7) =
b) -04 razy ⅖ - 4,6 + 2¼ =
c) (-½) [ (- ⅕ + 4,2 ) - ( 0,6 razy ¼) ] =
d) - 7,6 razy ( 0,5 + ¾) =
e) ⅗ : ( 2 razy 0,13) =
f) (-3,1) razy 0,6 + (- pięć drugich ) : (⅖) =


z gÓry b. dziękuje ;)))

2

Odpowiedzi

2009-05-12T20:55:11+02:00
Z obliczeniami :

a) 0.2 x (¾ x osiem szóstych [ tutaj musisz skrócić 3 z 6 i 4 z 8 ] - 4,5 + 7) = 0.2x ( 1 - 4,5 + 7) = 0,2 x 3,5 = 0,7
b) -0,4 razy ⅖ - 4,6 + 2¼ =-0,4 x 0,4-4,6+2,25=0,16-4,6+2,25=-2,19
c) )(-½) x (- ⅕ + 4,2 ) - ( 0,6 x ¼) =(-½) x (-0,2 + 4,2 ) - ( 0,6*0,25) =(-½) x [4 - 0,15]= (-½) x 3,85= -1,925
d) - 7,6 x ( 0,5 + 0,75) = - 7,6 x 1,25 = - 9,5
e) 0,6 : ( 2 x 0,13) = 0,6 : 0,26 = 0,23
f) (-3,1) x 0,6 + (-5/2) : (⅖) = -1,86 - 6,25 = -8,11

2009-05-12T21:00:55+02:00
A) 0,2*(¾ : 6/8 + 2,5 )=0,2*(3/4*8/6+2,5)=0,2*(1+2,5)=0,2*3,5=0,7
b) -0,4 razy ⅖ - 4,6 + 2¼ =-0,4*0,4-4,6+2,25=0,16-4,6+2,25=-2,19
c)(-½)*[ (- ⅕ + 4,2 ) - ( 0,6 razy ¼) ]=(-½)*[ (-0,2 + 4,2 ) - ( 0,6*0,25) ]=(-½)*[4-0,15]=(-½)*3,85=-1,925
d) - 7,6*( 0,5+0,75) = -7,6*1,25=9,5
e) 0,6 : ( 2*0,13) = 0,6:0,26≈0,23
f) (-3,1) * 0,6 + (-5/2) : (⅖) = -1,86-6,25=-8,11